2020
DOI: 10.5937/ejae17-27360
|View full text |Cite
|
Sign up to set email alerts
|

Tourist satisfaction with quality of service, food, atmosphere, and value for money in restaurants of major cities of the Western Balkans

Abstract: An important factor in modern-day tourism is restaurant guests' feeling of satisfaction. Motivated by the desire to quantify this feeling and make it an operational element of recommendations for further development of one segment of restaurant tourism, this paper examines the expressed satisfaction of foreign tourists in restaurants of selected cities in the Western Balkans. The second goal of this paper is to show the extent to which local visitors and domestic tourists are satisfied with the service provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
1
0
1
Order By: Relevance
“…Previous research has shown that perceived value plays a significant role in predicting satisfaction (Gallarza et al, 2013; Jin et al, 2015). There is consensus within the tourism literature that service quality and perceived value predict customer satisfaction (see, for example, Chen and Chen, 2010; El-Adly, 2019; Leonnard, 2018; Mafi et al, 2020; Živadinović, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous research has shown that perceived value plays a significant role in predicting satisfaction (Gallarza et al, 2013; Jin et al, 2015). There is consensus within the tourism literature that service quality and perceived value predict customer satisfaction (see, for example, Chen and Chen, 2010; El-Adly, 2019; Leonnard, 2018; Mafi et al, 2020; Živadinović, 2020).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Com consumidores cada vez mais exigentes a busca por inovações para atrair e mantêlo devem ser constantes (KAEWMAHAPHINYO; NUANGJAMNONG; DOWPISET, 2020;ŽIVADINOVIĆ, 2020). Além disso, com a variedade e número de concorrentes do setor, as empresas devem ser capazes de criar estratégias de sobrevivência atendendo a demanda dos diferentes públicos que consomem o produto (SOLUNOĞLU, 2020).…”
Section: Introductionunclassified